Appendix 2.1: Celsa Hilao, et al. v. Estate of Ferdinand E. Marcos - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Getting an “authentic” copy of this judgement online is difficult. The following was reproduced from a copy uploaded by columnist/blogger Tonyo Cruz. Another (HTML) copy can be found in the blog Martial Law Files: A History of Resistance (martiallawfiles.wordpress.com/classsuit/hawaii-civil-class-suit-vs-the-estate-of-marcos-1986/final-judgementjanuary-27-1995). Counter-checking the fidelity of these reproductions was done by looking at an authentic-looking “offline” copy, found in the cumbersome pro-Marcos tome Let the Marcos Truth Prevail. This is how the book’s unknown editors/compilers described the decision: “Final Judgment of Judge Manuel Real for compensatory damages to some 10,000 human rights claimants without giving a chance for the defendant Estate of Ferdinand Marcos to present and rebut plaintiff’s evidences in gross violation of due process” (emphasis his/her/theirs) (c2004, 297). However, as appendix 2.3 shows, that was not the case.